THE ENERGY SPECTRUM OF CHARGE CARRIERS IN IDEAL CRYSTALS (International journal of artificial intelligence, 2025)
In solid-state physics, understanding how electrons and holes—collectively called charge carriers—behave inside crystalline materials is essential for explaining many of their physical properties. These properties include electrical conductivity, optical absorption, and heat transfer. One of the most fundamental concepts used to describe charge carrier behavior is the energy spectrum, which defines the set of possible energy levels that these particles can occupy. In ideal crystals, this spectrum takes on a clear and regular structure, allowing scientists to analyze materials with precision.